Whose Responsibility? Community anti-racism strategies after September 11, 2001 - Dreher, Tanja (UTS Shopfront Series, 2006)
This research monograph documents and analyses the many ways in which communities experiencing racism after September 11, 2001 have responded to increased prejudice, harassment and discrimination. While much research analyses the 'problem' of racism, this book highlights the responses developed by targeted communities, including strategies of Interfaith, cross-cultural education, media responses and community cultural development work. A follow-up to the 2006 work Targeted, the research underlying this book is based on extensive community consultations and interviews with Arab, Muslim and Sikh communities in Sydney. It maps the field and identifies common challenges with the aim of contributing to wider processes of innovation in community anti-racism work.